Checklist of Turkish Opiinae (Hymenoptera, Braconidae) - Beyarslan, Ahmet; Fischer, Maximilian (Zootaxa, 2013)
The Opiinae (Hymenoptera: Braconidae) species recorded from Turkey until the end of 2011 are listed, the present total number being 182. Changes with respect to the previous Turkish fauna are briefly annotated and the distributions for all the species in each of the 68 biogeographical provinces of Turkey are presented. After the publication of our previous fauna, 174 species have been recorded as new to Turkey. Of these, 105 species are distributed only in Asian Turkey and ten species are distributed only in European Turkey, while 73 species occur in both. The presented checklist covers synonyms, zoogeographical region(s), hosts, host plants of the host species and parasitoid data for the species. In total, 182 species belonging to ten genera are reported for Turkey. The number of species of each genus is represented by: Atormus van Achterberg, 1997: one; Biosteres Foerster, 1862: 17; Bitomus Szépligeti, 1910: three; Diachasma Foerster, 1862: one; Diachasmimorpha Viereck, 1913: one; Eurytenes Foerster, 1862: three; Indiopius Fischer, 1966: three; Opius Wesmael, 1835: 151, Psyttalia Walker, 1860: one; Sternaulopius Fischer, 1965: one.